Skeleton-Structure WS2@CNT Thin-Film Hybrid Electrodes for High-Performance Quasi-Solid-State Flexible Supercapacitors - Yang, Xinyu; Li, Jiahui; Hou, Chengyi; Zhang, Qinghong; Li, Yaogang; Wang, Hongzhi (Frontiers in Chemistry, 2020)
The purpose of this work is to explore the application prospect of WS2 as active material in flexible electrode. Since WS2 has the similar disadvantages as other two-dimensional layered materials, such as easily stacking, it is essential to develop three-dimensional structure of its assembly in terms of electrochemical performance. In addition, low conductivity of WS2 still limits its application as flexible electrodes. In order to solve these problems, carbon nanotubes (CNTs) are introduced to improve the conductivity of the hybrid WS2 materials, and to construct a skeleton structure in WS2 assembly. Compared with pure CNTs and WS2, the WS2@CNTs thin-film hybrid with unique skeleton structure has a high specific area capacitance that reaches the maximum 752.53 mF/cm 2 at scan rate 20 mV/s. Meanwhile, this hybrid electrode material shows good stability of 10, 000 cycles with only 1.28% loss of its capacitance. In order to prove its feasibility in practical application, a quasi-solid-state flexible supercapacitors is assembled, and its electrochemical characteristics (specific area capacitance is 574.65 mF/cm 2 ) and bendability (under 135 ° bend for 10, 000 times, 23.12% loss at a scan rate of 100 mV/s) are further investigated and proved potential in this field.